Sustainability Analysis of Water Availability in Way Sekampung Dam using Vensim Dynamic Program - Sefrinta Sasma Murdiagatma; Endro Prasetyo Wahono; Dyah Indriana Kusumastuti; Ofik Taupik Purwadi; Ahmad Zakaria (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
The sustainability of dam operations needs to be reviewed in terms of water availability, in order to maintain the sustainability of water demand in all sectors in the coming years. This study aims to analyze of water availability of the Way Sekampung Dam reservoir according to its needs using one of the applications of the dynamic program, Vensim. The study used data-driven scenario simulations on the Vensim application, to analyze key factors including available inflows, required outflows, storage capacity of the dam and plans to supply raw water over a 25-year period. The results show that the dam can supply raw water for Bandar Lampung, Beranti, Pringsewu and Metro City with a total capacity of 2,737 liters per second and support water needs for potential irrigation of 76,006 hectares. Optimization of the dam's storage operation can be achieved, with a target reliability of 100% occurring in 2027, the year when the dam's storage condition reaches its optimal level at an elevation of +125.23 meters. To meet downstream water demand, the dam's storage capacity must be maintained at an elevation of +124.0 meters or higher, with a volume of 68,060,000 m³ and an inundation area of 5,020.8 km2. If the water storage falls below this elevation, it will be necessary to update the water allocation policy, adjust management regulations, appropriate management strategies, including periodic updating of the reservoir operation rules and implementation of a flexible water release schedule, to ensure continuous water availability at the Way Sekampung Dam reservoir.